Aphodius petri: a replacement name for the primary junior homonym Aphodius kozlovi Frolov, 2009 (Coleoptera: Scarabaeidae: Aphodiinae) - Frolov, Andrey V. (Zootaxa, 2014)
The alpine scarab beetle Aphodius (Agolius) kozlovi was described from Eastern Tibet, China from the materials collected by the Central Asian expedition (1899–1901) led by Petr Kuz’mich Kozlov (Frolov 2009). The new species was named after Kozlov, but I had overlooked Aphodius (Acrossidius) kozlovi Koshantschikov, 1916. Hence, Aphodius (Agolius) petri, new name is here proposed as a replacement name for Aphodius kozlovi Frolov, 2009. As the replaced name, the new name is patronymic after Petr Kuz’mich Kozlov.